2016
DOI: 10.1128/aem.01151-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Microbial Communities in Iron-Dominated Flocculent Mats in Deep-Sea Hydrothermal Environments

Abstract: It has been suggested that iron is one of the most important energy sources for photosynthesis-independent microbial ecosystems in the ocean crust. Iron-metabolizing chemolithoautotrophs play a key role as primary producers, but little is known about their distribution and diversity and their ecological role as submarine iron-metabolizing chemolithotrophs, particularly the iron oxidizers. In this study, we investigated the microbial communities in several iron-dominated flocculent mats found in deep-sea hydrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 90 publications
2
27
0
Order By: Relevance
“…The two other groups are composed of communities from Snail, Urashima, and NW Rota-1, which are all relatively close to one another whereas NW Eifuku is hundreds of km north of these three vent fields (Figure 1A ). These data support previous research showing community structure variability corresponding with vent location (Opatkiewicz et al, 2009 ; Huber et al, 2010 ; Makita et al, 2016 ). Although there were OTUs with significantly different abundances among all three groups of iron-dominated mats as determined via Metastats (Figure 3 ), there were no genera unique to one grouping, which suggests that a common ecosystem function is shared among the abundant community members of the Zeta-, Epsilon-, and Gamma-proteobacterial OTUs in all iron-dominated mats of the Mariana Arc and back-arc.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The two other groups are composed of communities from Snail, Urashima, and NW Rota-1, which are all relatively close to one another whereas NW Eifuku is hundreds of km north of these three vent fields (Figure 1A ). These data support previous research showing community structure variability corresponding with vent location (Opatkiewicz et al, 2009 ; Huber et al, 2010 ; Makita et al, 2016 ). Although there were OTUs with significantly different abundances among all three groups of iron-dominated mats as determined via Metastats (Figure 3 ), there were no genera unique to one grouping, which suggests that a common ecosystem function is shared among the abundant community members of the Zeta-, Epsilon-, and Gamma-proteobacterial OTUs in all iron-dominated mats of the Mariana Arc and back-arc.…”
Section: Discussionsupporting
confidence: 92%
“…All characterized Zetaproteobacteria strains are obligate iron-oxidizing lithoautotrophs belonging to the genus Mariprofundus (Emerson et al, 2007 ; McBeth et al, 2011 ; Makita et al, 2017 ). Members of this genus have been previously detected in flocculent mats from the back-arc Snail and Urashima sites and from NW Eifuku (Davis and Moyer, 2008 ; Kato et al, 2009a ; Makita et al, 2016 ); in addition to these locations, we have now identified Zetaproteobacteria at NW Rota-1 (Olde Iron Slides). After years of documented eruptions from 2004 to 2010 (Schnur et al, 2017 ), it is possible the hydrothermal fluids are undergoing a transition from sulfur- to iron-dominated effluent at this location as hypothesized by Butterfield et al ( 1997 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To this end, we turned to Zetaproteobacteria in natural Fe microbial mats. The Zetaproteobacteria discovered to date are all considered to be Fe oxidizers, since every isolate grows by Fe oxidation and uncultured Zetaproteobacteria are typically found in Fe-oxidizing environments (10,(16)(17)(18)(19)(20)(21). The Zetaproteobacteria are often the dominant organisms in marine hydrothermal Fe mats (22)(23)(24)(25), where they play a key role in mat formation (26).…”
mentioning
confidence: 99%
“…A variety of Fe (oxyhydr)oxide forms and crystallinities coexist in soils and can be transformed to one another as a result of Fe redox cycling driven by both abiotic and biotic processes (Fortin and Langley, 2005;Kappler and Straub, 2005). The biotic transformations of Fe (oxyhydr)oxides mediated by microorganisms in most soils and sediments are often much faster than the corresponding abiotic reactions (Weber et al, 2006a).…”
Section: Microbially Mediated Iron Redox Cyclingmentioning
confidence: 99%